A 3D Voronoi and subdivision model for calibration of rock properties. (27th October 2017) - Zhu, De-Fu; Tu, Shi-Hao; Ma, Hang-sheng; Zhang, Xin-wang
Abstract: Rock cleavages consist of the cracks between blocks and the internal faults in blocks. The built-in modeling module in the Three-dimension Distinct Element Code cannot accurately describe the internal structure and the cleavage development characteristics of rock. This study combined 3D Voronoi block elements and scanning electron microscope images, to construct a numerical model equivalent to the rock meso structures. Three strategies are proposed to refine the initial model by block subdivision to achieve a function that allows cleavages in the model to cross through the blocks. A physical uniaxial compression test was performed in the laboratory to calibrate the mechanical parameters of the siltstone and the calibrated parameters then were validated by a Brazilian disc test. Sensitivity analysis was conducted to investigate the relationship between the meso-parameters and the model's macro-response, and a calibration procedure was established for accurate replication of rock mechanical behavior. The statistics and analyses of failure characteristics for joints in the model showed that when the compressive and tensile strength values peaked, the percentages of tensile failures were approximately 37% and 10%, respectively. Comparing the cleavages after sample failure in lab tests with the cleavage development paths predicted by the models, the compressive and tensile characteristics were analyzed and the results confirmed the reliability of applying the 3D Voronoi block and subdivision modeling method in the numerical simulation study of the mechanical properties of the rock.